Post-carvedilol myocardial function in cats with obstructive hypertrophic cardiomyopathy - Saito, Takahiro; Suzuki, Ryohei; Yuchi, Yunosuke; Fukuoka, Haru; Satomi, Shuji; Teshima, Takahiro; Matsumoto, Hirotaka (Frontiers in Veterinary Science, 2025)
IntroductionHypertrophic cardiomyopathy (HCM) is the most prevalent cardiac disease in cats, and one phenotype includes obstructive HCM with dynamic left ventricular outflow tract obstruction (DLVOTO). Myocardial function has been reported to be lower in cats with obstructive HCM than in non-obstructive HCM. Carvedilol, because of its pharmacological action, is expected to reduce the pressure gradient associated with DLVOTO, but no previous reports have studied its effects on myocardial function. This study aimed to evaluate myocardial function in cats with obstructive HCM with left ventricular outflow tract obstruction treated by carvedilol administration.MethodsThis retrospective observational study included 16 cats with obstructive HCM and subsequent treatment of DLVOTO with carvedilol. In addition to conventional echocardiography, strain and strain rates in the left ventricular longitudinal and circumferential directions were measured using layer-specific two-dimensional speckle tracking echocardiography. Each variable was then compared before and after carvedilol medication.ResultsSystolic anterior motion of the mitral valve disappeared in 14 cats and all cats showed resolved DLVOTO with maximal left ventricular outflow tract blood flow velocity of <2.5 m/s after carvedilol administration (P < 0.01). Circumferential strain in the epicardial layer and in the whole layer was significantly increased after carvedilol administration (P < 0.01, P = 0.04, respectively). In contrast, systolic longitudinal strain showed no significant difference between before and after carvedilol administration.ConclusionTreatment of obstructive HCM with carvedilol improved DLVOTO and myocardial function without a negative inotropic effect. Carvedilol may be effective in treating cats with obstructive HCM.